TECHNICAL INSTRUCTIONS IN ENGLISH: VOICES OF TECHNICAL LECTURERS - Sanmugam, S.Thivviyah; Raja Harun, Raja Nor Safinas (Journal of Technical Education and Training, 2013)
This descriptive study examined the perceptions of technical lecturers towards the teaching of technical modules in English at a polytechnic in Malaysia. A questionnaire consisting four main aspects of perceptions mainly readiness, attitudes, problems and training needs were used for the purpose of data collection. Data were collected from 75 technical lecturers through the questionnaires, which were then analyzed to get the value of  frequency and percentage score meanwhile interview data were qualitatively analysed with initial descriptive codes being assigned to lecturers’ responses. This study will allow relevant authorities to identify the perceptions and training needs of the technical lecturers and to provide appropriate in-service training in order to facilitate these lecturers who are entering the new domain of teaching content subjects using English as the medium of intruction.